HEALING CONCEPT IN NURSING AND THE RELATED THEORIES - Akhmedova Shakhodat Makhmutovna (Journal Park Publishing, 2024)
Healing is a general and complex concept that depends on culture and society. The article organized the theoretical knowledge that nurses can play a major role in helping patients to heal through compassion, kindness and proper communication, and also emphasized Islamic views.
Keywords: concept, healthcare, nursing, disease, culture, analyzing, providing spiritual care, culture and community